2018
DOI: 10.1016/j.immuni.2017.11.026
|View full text |Cite
|
Sign up to set email alerts
|

Chanzyme TRPM7 Mediates the Ca2+ Influx Essential for Lipopolysaccharide-Induced Toll-Like Receptor 4 Endocytosis and Macrophage Activation

Abstract: Toll-like receptors (TLRs) sense pathogen-associated molecular patterns to activate the production of inflammatory mediators. TLR4 recognizes lipopolysaccharide (LPS) and drives the secretion of inflammatory cytokines, often contributing to sepsis. We report that transient receptor potential melastatin-like 7 (TRPM7), a non-selective but Ca-conducting ion channel, mediates the cytosolic Ca elevations essential for LPS-induced macrophage activation. LPS triggered TRPM7-dependent Ca elevations essential for TLR4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
163
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 197 publications
(187 citation statements)
references
References 62 publications
7
163
0
Order By: Relevance
“…Our results also suggested that Mg could reduce endothelial cell leakage induced by LPS in vitro through suppressing NF-κB signaling pathway. It was reported that Ca ions influx was necessary for NF-κB activation and translocation to nuclear in both macrophages [65] and endothelial cells [66]. Influx of extracellular Ca 2+ via TRPV4/ 5 (Transient receptor potential cation channel subfamily V members) channels in cell membrane was also necessary in RANKL induced osteoclast differentiation [67,68].…”
Section: Discussionmentioning
confidence: 98%
“…Our results also suggested that Mg could reduce endothelial cell leakage induced by LPS in vitro through suppressing NF-κB signaling pathway. It was reported that Ca ions influx was necessary for NF-κB activation and translocation to nuclear in both macrophages [65] and endothelial cells [66]. Influx of extracellular Ca 2+ via TRPV4/ 5 (Transient receptor potential cation channel subfamily V members) channels in cell membrane was also necessary in RANKL induced osteoclast differentiation [67,68].…”
Section: Discussionmentioning
confidence: 98%
“…Here, we describe a version of a flow cytometry-based method that was initially reported by Kagan and colleagues (Kagan et al, 2008), and used by others, to monitor TLR4 endocytosis. We have used the method recently to study the role of transient receptor potential melastatin-like 7 (TRPM7), an ion channel, in TLR4 endocytosis (Schappe et al, 2018). The experimental logic of this method relies on measuring the loss of TLR4 and CD14 staining at the cell surface after LPS treatment.…”
Section: [Background]mentioning
confidence: 99%
“…Characteristic TLR4 and CD14 endocytosis measured over time in bone-marrow derived macrophages. Data was modified from its original presentation in Schappe et al ., 2018 with author permission.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…TRPV4 appears to negatively regulate LPS‐induced inflammation, but enhances both LPS‐mediated phagocytosis and ox‐LDL uptake . In contrast, a recent study found that TRPM7 positively regulates LPS‐induced inflammatory activation by enhancing endocytosis of the LPS‐TLR4 complex, and its depletion has been shown to protect mice from LPS‐induced peritonitis . Finally, manipulation of the expression and activity of TRPV2 and TRPC6 reveals that these channels are required for phagocytosis in macrophages .…”
Section: Molecular Mechanisms Of Mechanotransductionmentioning
confidence: 96%